2010
DOI: 10.1002/hed.21503
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder function in patients undergoing selective neck dissection with or without radiation and chemotherapy

Abstract: Selective neck dissection can have a negative effect on shoulder function despite spinal accessory nerve preservation. Adjuvant therapy does not contribute additional detriment to shoulder function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 26 publications
1
22
1
Order By: Relevance
“…Our data suggest that use of radiation therapy and/or chemotherapy is correlated with poorer shoulder function and quality of life. This is in contrast to findings from Watkins et al, 18 in which shoulder impairment was documented in patients who underwent SND, but there was no significant effect for patients who received adjuvant therapy. In the study by Watkins et al, radiation therapy and chemotherapy did not confer poorer shoulder function, but the total sample was 34 patients, and only 7 of these patients had neck dissection alone.…”
Section: Discussioncontrasting
confidence: 56%
“…Our data suggest that use of radiation therapy and/or chemotherapy is correlated with poorer shoulder function and quality of life. This is in contrast to findings from Watkins et al, 18 in which shoulder impairment was documented in patients who underwent SND, but there was no significant effect for patients who received adjuvant therapy. In the study by Watkins et al, radiation therapy and chemotherapy did not confer poorer shoulder function, but the total sample was 34 patients, and only 7 of these patients had neck dissection alone.…”
Section: Discussioncontrasting
confidence: 56%
“…Others have shown that disability improved with time, and rehabilitation played an important role in promoting function and reducing pain. 9,[21][22][23][24] Some studies have focused on wrist mobility, but the effect of RFF flap harvest on this parameter is unclear. [7][8][9][10] In addition, it has been shown that objective measurements do not accurately reflect the patient's experience.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Once developed, shoulder-related symptoms have been found to persist rather than improve even in cases of SAN recovery, and little is known about effective management of this condition over the long term. 2,11 The results from our randomized controlled trial of upper extremity (UE) progressive resistance exercise training (PRET) demonstrated significant improvements in patient-rated shoulder pain and disability, UE strength and endurance, and range of motion in post-surgical HNC survivors. 12 All other outcomes, including fatigue, neck dissection impairment, and quality of life (QOL), favoured the PRET group at the end of the 12-week intervention but did not reach statistical significance.…”
Section: Ré Sumémentioning
confidence: 99%